Transition Economy: Urbanization, the Processes of Creation and Accumulation of Property - Melnikas, Borisas (Ekonomika, 2005)
The urgent problems of urban development and the processes of property creation and accumulation in the context of economic, social, political transformations in the society are analyzed. The possibilities of multicriteria strategic decision-making are described. The following objects are analyzed: urban development under the conditions of transformations as the major research object in the area of strategic property management; cities and their development as an environment of property creation and accumulation; transformation processes as the general context of urban development and of the creation and accumulation of property; the major trends of the transformation processes in Central and Eastern Europe, their main criteria and indicators; the evaluation criteria used in the area of urban development and property strategic management in the conditions of transformation processes; multicriteria decision-making in the area of urban development and property strategic management.